2021
DOI: 10.1055/a-1404-3610
|View full text |Cite
|
Sign up to set email alerts
|

Family planning with inflammatory bowel disease: the challenge of childlessness and parent concerns

Abstract: Background In patients with inflammatory bowel disease (IBD), diagnosis is often established at the beginning of childbearing age. Accordingly, concerns about family planning and pregnancy (FPP) are common. Poor knowledge regarding FPP might contribute to increased childlessness in patients with IBD. Methods The Crohn’s and Colitis Pregnancy Knowledge Score (CCPKnow, 17 multiple-choice questions) was translated into German and then used for a web-based survey. Childlessness was analyzed with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“… 32 Evidence on the association between parity and chronic conditions is limited, but it does suggest that the prevalence of having children is up to 22% lower in affected women. 33 36 Thus, omitting parity from the analysis may result in confounding of the OR between chronic conditions and urinary incontinence. Previous work has shown that the size of this confounding bias, termed the relative risk due to confounding (RR C ), can be estimated using 3 values: the prevalence of the confounder in both the exposed and unexposed, and the association between the confounder and the outcome.…”
Section: Methodsmentioning
confidence: 99%
“… 32 Evidence on the association between parity and chronic conditions is limited, but it does suggest that the prevalence of having children is up to 22% lower in affected women. 33 36 Thus, omitting parity from the analysis may result in confounding of the OR between chronic conditions and urinary incontinence. Previous work has shown that the size of this confounding bias, termed the relative risk due to confounding (RR C ), can be estimated using 3 values: the prevalence of the confounder in both the exposed and unexposed, and the association between the confounder and the outcome.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to providing standard antenatal education, counseling should address patient misconceptions about infertility, medication safety, maternofetal complications, and IBD heritability, which are common concerns in IBD patients and contribute toward VC. [96][97][98][99] This is associated with improved medication adherence, folic acid supplementation, smoking cessation, reduced disease flares during pregnancy, and improved neonatal outcomes. [100][101][102] In women actively contemplating pregnancy, medication review for risk of teratogenicity and objective assessment of disease activity should be performed prior to conception, aiming to confirm disease remission to optimize pregnancy outcomes.…”
Section: Preconception Managementmentioning
confidence: 99%
“…Feeling unable to cope with the added responsibility of looking after a child or concerns about pregnancy, such as the risks of medication with respect to pregnancy or potential heredity of IBD, are frequently reported. [12][13][14] These facets impose a significant extra burden on patients, while remaining challenging to quantify.…”
Section: How Might It Impact On Clinical Practice In the Foreseeable ...mentioning
confidence: 99%